IMPLEMENTASI KURIKULUM MERDEKA BELAJAR SISWA SISWI SDN 02 CIHERANG - Effendi, Absarani Maharani; Hardjo, Ayra Diputera; Edang, Ignasius Alfon Hanjuk; Rajasa, Daud Angga; Arisandi, Desi (Jurnal Serina Abdimas, 2023)
It is not an easy thing for schools to change the curriculum, as currently the government is changing the curriculum from the previous curriculum, namely the 2013 Curriculum (K-13) to the new curriculum, the Merdeka Belajar Curriculum. The Merdeka Curriculum aims to create diverse intracurricular learning, where the content will be more optimal so that students have enough time to deepen concepts and strengthen competencies, whereas for the 2013 curriculum teachers are required to seek as much knowledge as possible because rapid technological developments make it easier for students to learn. get information. This curriculum transition is also felt by the teacher of grade 1 and grade4 of Elementary School 02 Ciherang, where the teacher need time to understand and implement the Merdeka Curriculum as a reference for teaching and learning activities. This reason is the background for students in Group 02 MBKM KKN- T Tarumanagara University carrying out community services to help teachers and students get to know the curriculum they will use in the future. The activities carried out by Group 02 MBKM KKN-T Students are to hone the intrapersonal and cognitive interaction skills that exist in children, as well as to apply teaching materials through media that activate student responses and generate student learning motivation. The activities carried out are project-based learning, namely by providing science projects to improve students' knowledge and skills. The project given is the Bean Sprouts Planting project where students study the growth stages of plant life. This bean sprout planting project also supports the learning of Natural Sciences and the activity is attended by students from grade 1 and grade 4 accompanied by students from Group 02 MBKM KKN-T. The results obtained after the program was implemented were an increase in students' response and enthusiasm for learning outside the classroom. Students also actively ask questions about planting bean sprouts. From this activity it can be concluded that learning outside the classroom can be applied to increase the response of grade 1, grade 4 and grade 6 students at Ciherang 2 Elementary School to learning material. ABSTRAK Bukan hal yang mudah bagi Sekolah ketika melaksanakan pergantian kurikulum, seperti saat ini dimana pemerintah melakukan perubahan kurikulum dari kurikulum terdahulu yaitu Kurikulum 2013 (K-13) menjadi kurikulum yang baru Kurikulum Merdeka Belajar. Kurikulum Merdeka ialah bertujuan agar terciptanya pembelajaran intrakurikuler yang beragam, dimana konten akan lebih optimal agar peserta didik memiliki cukup waktu untuk mendalami konsep dan menguatkan kompetensi, sedangkan untuk kurikulum 2013 guru dituntut untuk mencari pengetahuan sebanyak – banyaknya karena perkembangan teknologi cepat membuat siswa lebih mudah dalam mendapatkan informasi. Transisi kurikulum ini juga dirasakan oleh tenaga pengajar kelas 1 dan kelas 4 Sekolah Dasar Negeri 02 Ciherang, dimana para tenaga ajar membutuhkan waktu untuk memahami dan mengimplementasikan Kurikulum Merdeka sebagai acuan kegiatan belajar – mengajar. Alasan ini melatarbelakangi mahasiswa/i Kelompok 02 MBKM Kuliah Kerja Nyata - Tematik Universitas Tarumanagara melaksanakan kegiatan kepada masyarakata untuk membantu para guru dan murid dalam mengenal kurikulum yang akan mereka gunakan kedepannya. Kegiatan yang dilakukan oleh Mahasiswa/I Kelompok 02 MBKM KKN-T adalah untuk mengasah kemampuan interaksi intrapersonal serta kognitif yang ada pada diri anak – anak, serta untuk mengaplikasikan materi ajar melalui media yang sifatnya mengaktifkan respon siswa serta membangkitkan motivasi belajar siswa. Kegiatan yang dilaksanakan adalah pembelajaran berbasis project yaitu dengan memberikan project sains untuk meningkatkan pengetahuan dan keterampilan siswa. Project yang diberikan yaitu project Penanaman Tanaman Tauge dimana siswa mempelajari tahap pertumbuhan hidup tanaman. Project penanaman tanaman tauge ini mendukung pula pembelajaran Ilmu Pengetahuan Alam dan kegiatan diikuti oleh murid – murid kelas 1 dan kelas 4 didampingi oleh mahasiswa/i Kelompok 02 MBKM KKN-T. Hasil yang dapatkan setelah program tersebut terlaksana adalah meningkatnya respon dan antusias murid – murid pada pembelajaran di luar kelas. Siswa juga aktif bertanya mengenai Penanaman Tanaman Tauge. Dari kegiatan ini dapat disimpulkan bahwa pembelajaran di luar kelas dapat diterapkan untuk meningkatkan respon siswa kelas 1, kelas 4 dan kelas 6 Sekolah Dasar Negeri Ciherang 2 terhadap suatu materi pembelajaran.